Hyperintensities of the Optic Radiation on T2-Weighted MR Images of Elderly Subjects - Kitajima, Mika; Korogi, Yukunori; Okuda, Tomoko; Shiraishi, Shin-ya; Ikeda, Osamu; Morishita, Shoji; Takahashi, Mutsumasa; Eto, Komyo (American Journal of Neuroradiology, 1999)
BACKGROUND AND PURPOSE: Although abnormal hyperintensities are frequently observed at or around the optic radiation in elderly subjects, no previous reports have mentioned the clinical significance and pathologic changes of these hyperintensities. We evaluated the hyperintensity patterns of the optic radiation and its surrounding structures on T2-weighted MR images and compared these findings with pathologic observations and visual field measurements.METHODS: High-resolution coronal T2-weighted MR images of 102 consecutive patients (51–84 years old) were evaluated retrospectively for the presence and morphology of hyperintensities of the optic radiation (204 sides) and its surrounding structures. Pathologic specimens were obtained from 25 other patients (60–91 years old) who had died of nonneurologic causes. The histopathologic changes of the optic radiation and its surrounding structures were evaluated and correlated with the MR findings. Finally, MR findings and visual field measurements were correlated in 46 elderly volunteers (70–91 years old).RESULTS: Hyperintensities of the optic radiation or its surrounding structures or both were observed on 125 sides (93%) of 67 patients (61%), and linear/laminar hyperintensity of the optic radiation and the tapetum was the characteristic finding. Eleven (44%) of 25 pathologic specimens exhibited pallor of three anatomic layers (the external sagittal stratum or the optic radiation, the internal sagittal stratum, and the tapetum). No subjects with hyperintensity of the optic radiation had visual field abnormalities.CONCLUSION: Linear/laminar hyperintensity of the optic radiation and tapetum on T2-weighted images is common in elderly subjects, and may reflect differences in the internal structures and in the water content of three anatomic structures. Hyperintensities of this region did not cause visual field abnormalities in a group of elderly volunteers.